1997
DOI: 10.3801/iafss.fss.5-59
|View full text |Cite
|
Sign up to set email alerts
|

An Overview Of Research On Wildland Fire

Abstract: This paper outlines the subject matter of research on the physics and phenomenology of' wildland fire, focusing on topics that bear upon issues of fire control and fire safety. Motivations for research on fire phenomenology are identified as arising from the activities necessary to achieve fire-related objectives, including acceptable levels of fire safety. Differences in the activities, techniques, and tactical objectives for control and prevention of' fires in natural fuels and in manmade structures are note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Several knowledge gaps have been alluded to throughout this summary. Furthermore, many basic wildland fire behavior research needs identified some 30 years ago, some of which are relevant to crown fires, have yet to be addressed (e.g., Albini 1984Albini , 1997Alexander and Andrews 1989;Van Wagner 1985).…”
Section: Future Outlookmentioning
confidence: 99%
“…Several knowledge gaps have been alluded to throughout this summary. Furthermore, many basic wildland fire behavior research needs identified some 30 years ago, some of which are relevant to crown fires, have yet to be addressed (e.g., Albini 1984Albini , 1997Alexander and Andrews 1989;Van Wagner 1985).…”
Section: Future Outlookmentioning
confidence: 99%
“…Modeling of combustion and transport in wildland fIres has evolved signifI· cantly in the past several decades, and a relatively recent review summarizes the pro· gress (Albini, 1997). While early work was rather approximate (e.g., Fons, 1946;Emmons, 1964;Hottel et aI., 1965;Rothermel, 1972;Sullivan et ai., 2002, Cekirge, 1978, more recent studies have sought to develop physically·based modeling strate· gies (Albini, 1985;Grishin et ai., 1986;Weber, 1989Weber, , 1991Grishin, 1997;Baum and Mell, 1998;Porterie et ai., 2000;Bellemare et ai., 2001;Sullivan et ai., 2002;Catchpole et ai., 2002;Morvan and Dupuy, 2002;Porterie et aI., 2003;Butler et ai., 2004b;Linn and Cunningham, 2005).…”
Section: Introduction and Review Of Prior Workmentioning
confidence: 99%
“…Some of the research groups that have contributed to this special issue are already at the intersection between the two research areas. These are mainly university groups, and this trend is notably different from the situation 30 years ago when the principal organizations involved in research on wildfire behavior were government agencies [1].Wildfires are very complex phenomena and this perhaps discourages many researchers from tackling the related scientific problems. However, this special issue is the perfect showcase that many approaches used in fire safety engineering are highly relevant to wildfire research, and vice versa.…”
mentioning
confidence: 98%
“…Some of the research groups that have contributed to this special issue are already at the intersection between the two research areas. These are mainly university groups, and this trend is notably different from the situation 30 years ago when the principal organizations involved in research on wildfire behavior were government agencies [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation